The Demand for Electricity in Kuwait: A Cointegration Analysis - Alfalah, Osama; Alhumaidan, Lama; Baglan, Deniz (International Journal of Energy Economics and Policy, 2020)
In this paper, we investigate the determinants of electricity demand in Kuwait and evaluate their impact on electricity consumption. In order to do this, we use the standard demand equation, cointegration techniques, and the error correction model on annual time series data for Kuwait from 1972 to 2017. One of the important features of our contribution is that it covers the most recently available data, in which we use the longest annual period (45 years) compared to all other studies of electricity demand in the region. We find that income elasticity for Kuwaiti consumers is insignificant both in short-run and the long run. This indicates that income has no impact on the consumption of electricity in Kuwait. Additionally, the short-run price elasticity is -0.22 while the long-run is -1.22, suggesting a negative yet elastic relationship between the electricity price in Kuwait and the demand in the long-run, while the short-run is inelastic. Keywords: electricity demand, structural time series model, cointegration. JEL Classifications: C22, Q41, Q43 DOI: https://doi.org/10.32479/ijeep.9855